5
$\begingroup$

$$(1-x^2)y''-2xy'+p(p+1)y=0, p \in \mathbb{R} \text{ constant } \\ -1 < x<1$$

At the interval $(-1,1)$ the above differential equation can be written equivalently

$$y''+p(x)y'+q(x)y=0, -1<x<1 \text{ where } \\p(x)=\frac{-2x}{1-x^2} \\ q(x)= \frac{p(p+1)}{1-x^2}$$

$p,q$ can be written as power series $\sum_{n=0}^{\infty} p_n x^n, \sum_{n=0}^{\infty} q_n x^n$ respectively with centre $0$ and $\sum_{n=0}^{\infty} p_n x^n=p(x)$ and $\sum_{n=0}^{\infty} q_nx^n=q(x), \ \forall -1<x<1$

$$p(x)= \sum_{n=0}^{\infty} (-2) x^{2n+1}, -1<x<1$$

$$q(x)= \sum_{n=0}^{\infty} p(p+1) x^{2n}, \forall -1<x<1$$

Since $p,q$ can be written as power series with centre $0$ and radius of convergence $1$, it's logical to look for a solution of the differential equation of the form

$$y(x)=\sum_{n=0}^{\infty} a_n x^n \text{ with radius of convergence } R>0$$

$$-2xy'(x)= \sum_{n=1}^{\infty} -2n a_n x^n$$

$$y''(x)= \sum_{n=0}^{\infty} (n+2)(n+1) a_{n+2} x^n \\ -x^2y''(x)=\sum_{n=2}^{\infty} -n(n-1)a_nx^n$$

We have:

$$\sum_{n=0}^{\infty} \left[ (n+2)(n+1) a_{n+2}-n(n-1)a_n-2na_n+p(p+1)a_n\right]x^n=0, \forall x \in (-R,R)$$

It has to hold: $(n+2)(n+1)a_{n+2}-n(n-1)a_n-2na_n+p(p+1)a_n=0, \forall n=0,1,2, \dots$

Thus: $$a_{n+2}=-\frac{(p-n)(p+n+1)}{(n+1)(n+2)}a_n, \forall n=0,1,2, \dots$$

So the solution is written as follows:

$$y(x)=a_0 \left[ 1- \frac{p(p+1)}{2!}x^2+ \frac{p(p-2)(p+1)(p+3)}{4!}x^4- \frac{p(p-2)(p-4)(p+1)(p+3)(p+5)}{6!}x^6+ \dots \right] +a_1 \left[ x- \frac{(p-1)(p+2)}{3!}x^3+ \frac{(p-1)(p-3)(p+2)(p+4)}{5!}x^5-\frac{(p-1)(p-3)(p-5)(p+2)(p+4)(p+6)}{7!}x^7+ \dots\right]$$

We will show that if $p \in \mathbb{R} \setminus{\mathbb{Z}}$ then the power series at the right of $a_0,a_1$ have radius of convergence $1$ and so they define functions $y_1(x), y_2(x)$, that are infinitely many times differentiable at $(-1,1)$.

We have for $-1<x<1, x \neq 0$:

$$\left | \frac{a_{2(n+1)} x^{2(n+1)}}{a_{2n} x^{2n}}\right |= \left |- \frac{(p-2n)(p+2n+1)}{(2n+1)(2n+2)}\right| |x|^2 \to |x|^2<1$$

So the series $\sum_{n=0}^{\infty} \overline{a_{2n}} x^{2n}$ converges for $-1<x<1$

In the same way, we show that the series $\sum_{n=0}^{\infty} \overline{a_{2n+1}}x^{2n+1}$ converges for $-1<x<1$.

According to the above, if $p \in \mathbb{R} \setminus{\mathbb{Z}}$ the power series at the right of $a_0, a_1$ have radius of convergence $1$ and so they define functions $y_1(x), y_2(x)$ that are infinitely many times differentiable at $(-1,1)$.

Then we show that $y_1(x)$ converges and in the same way we could show that $y_2(x)$ converges.

But have we shown like that that the radius of convergence is $1$? And how do we deduce that the functions are infinitely many times differentiable?

Also what is meant with $\overline{a_{2n}}$?

Furthermore, what happens if $p \in \mathbb{Z}$?

EDIT: Couldn't we also write the solution $y$ in the following form?

$$y(x)= \sum_{k=0}^{\infty} a_{2k} x^{2k}+ \sum_{k=0}^{\infty} a_{2k+1} x^{2k+1}$$

where :

$$a_{2k}= \frac{\prod_{j=0}^{2k-1} (j+(-1)^{j+1} p)}{(2k)!}a_0$$

and

$$a_{2k+1}= \frac{\prod_{j=1}^{2k} (j+(-1)^j p)}{(2k+1)!}a_1$$

Or am I wrong?

If it is like that, applying the ratio test we would get:

For $n=2k$:

$$\left| \frac{\frac{\prod_{j=0}^{2k+1} (j+(-1)^{j+1} p) a_0 x^{2k+2}}{(2k+2)!}}{\frac{\prod_{j=0}^{2k-1} (j+(-1)^{j+1} p) a_0 x^{2k}}{(2k)!}}\right| = \left| \frac{(2k-p)(2k+1+p) x^2}{(2k+1)(2k+2)} \right| \to |x^2|<1$$

So the series $\sum_{k=0}^{\infty} a_{2k} x^{2k}$ converges for all $x$ such that $-1<x<1$.

Is it right so far?

If so,how do we deduce that if $p \in \mathbb{R} \setminus{\mathbb{Z}}$ then the power series at the right of $a_0,a_1$ have radius of convergence $1$ and so they define functions $y_1(x), y_2(x)$, that are infinitely many times differentiable at $(-1,1)$ ?

EDIT 2: If $p$ is a positive integer, then one of the series terminates and becomes polynomial.

For example if $p=7$, then $a_7, a_9, a_{11}, \dots, a_{2n+1}=0$ and so $\sum_{k=0}^{\infty} a_{2k+1} x^{2k+1}= a_1 x+ a_3 x^3+ a_5 x^5$, right?

So does this mean that in such a case it doesn't hold that the power series at the right of $a_0,a_1$ have radius of convergence $1$ and so they define functions $y_1(x), y_2(x)$, that are infinitely many times differentiable at $(-1,1)$?

$\endgroup$
2
+100
$\begingroup$

(a) you need to do one of the tests, ratio or root test to determine the radius of convergence for each. it will follow from recurrence relation for $a_n$ that you have.

(b) i don't know what is meant by $\bar {a_n},$ there are no complex numbers here.

(c) if $p$ is a positive integer, then one of the series terminates and become legendre polynomial.

$\endgroup$
  • $\begingroup$ You mean that if $p$ is a positive integer then one of $a_{2k}, a_{2k+1}$ will be equal to $0$ ? $$$$ If so then one of the series $\sum_{k=0}^{\infty} a_{2k} x^{2k}, \sum_{k=0}^{\infty} a_{2k+1} x^{2k+1}$ will terminate, right? $$$$ What do you mean that it will become Legendre polynomial? $\endgroup$ – evinda May 27 '15 at 16:23
  • $\begingroup$ I think I see what you mean with: one of the series terminates and become legendre polynomial. $$$$ So in this case doesn't it hold that the power series at the right of $a_0,a_1$ have radius of convergence $1$ and so they define functions $y_1(x),y_2(x)$, that are infinitely many times differentiable at (−1,1) ? $\endgroup$ – evinda May 27 '15 at 16:30
  • $\begingroup$ Is the radius of convergence also defined for a polynomial or only for infinite series? $\endgroup$ – evinda Jun 3 '15 at 18:42

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.